The education of racial relations in the curriculum: the Licensee Courses in Geography in Santa Catarina - Passos, Joana Célia dos (2019)
Geography as a field of knowledge contributes to the empowerment of individuals to construct their identity and their positioning and agency in the world. Thus, the discussion about race relations is essential for the perception of the need for structural changes in Brazilian society and to understand the urban segregation, the right to land and the social and economic dynamics of the population. Considering these aspects, the article analyzes the curricula of undergraduate courses in Geography of five Higher Education Institutions located in the State of Santa Catarina, seeking to understand how the racial issues in these courses are presented. Taking into account that these undergraduate programs aim at the qualification of teachers of basic education, we also analyze the legal texts that regulate the qualification of teachers in Brazil, as well as Geography and those that interpret and complement Law n. 10.639/03 regarding its application in order to observe the adequacy of the Geography courses. Based on the analyzed data, it was observed that although the current legislation and its curricular norms have assimilated in the body of their texts the racial issues as structuring and educational principles, the presence of knowledge and the discussion about them is still timid in these courses, which are, for the most part, fulfilling the minimum required by law.